The vest pocket guide to GAAP - Bragg, Steven M. (Hoboken, New Jersey : Wiley ; Chichester : John Wiley [distributor], 2011)
Quick answers to your GAAP questions The Vest Pocket Guide to GAAP is the handy pocket problem-solver that gives today's busy financial executives the GAAP advice they need in a quick-reference format
1. The financial statements -- 2. Assets, liabilities, and equity -- 3. Revenue and expenses -- 4. Special transactions
Includes index
Keywords: Accounting -- Standards -- United States -- Handbooks, manuals, etc